2011
DOI: 10.4049/jimmunol.1101344
|View full text |Cite
|
Sign up to set email alerts
|

TLR6-Driven Lipid Droplets in Mycobacterium leprae-Infected Schwann Cells: Immunoinflammatory Platforms Associated with Bacterial Persistence

Abstract: The mechanisms responsible for nerve injury in leprosy need further elucidation. We recently demonstrated that the foamy phenotype of Mycobacterium leprae-infected Schwann cells (SCs) observed in nerves of multibacillary patients results from the capacity of M. leprae to induce and recruit lipid droplets (LDs; also known as lipid bodies) to bacterial-containing phagosomes. In this study, we analyzed the parameters that govern LD biogenesis by M. leprae in SCs and how this contributes to the innate immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 51 publications
5
123
0
2
Order By: Relevance
“…These mechanisms exhibit similarities to M. bovis BCG infection during which lipid droplet biogenesis is induced (i) in a time and dose-dependent manner, (ii) by both live and dead mycobacteria, (iii) by mycobacterial cell wall components and (iv) in bacterium-associated Almeida et al 2009, Mattos et al 2010). Interestingly, we have shown that the mechanisms of lipid droplet induction by M. leprae in Schwann cells share similarities with those observed in macrophages, but also exhibit some differences (Table) (Mattos et al 2010(Mattos et al , 2011b. Lipid droplet biogenesis is induced in a time and dose-dependent manner and requires bacterial phagocytosis.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…These mechanisms exhibit similarities to M. bovis BCG infection during which lipid droplet biogenesis is induced (i) in a time and dose-dependent manner, (ii) by both live and dead mycobacteria, (iii) by mycobacterial cell wall components and (iv) in bacterium-associated Almeida et al 2009, Mattos et al 2010). Interestingly, we have shown that the mechanisms of lipid droplet induction by M. leprae in Schwann cells share similarities with those observed in macrophages, but also exhibit some differences (Table) (Mattos et al 2010(Mattos et al , 2011b. Lipid droplet biogenesis is induced in a time and dose-dependent manner and requires bacterial phagocytosis.…”
mentioning
confidence: 68%
“…The stimulation of TLR signalling by bacteria and bacterial molecules has been shown to promote the accumulation of lipids in macrophages in the form of lipid droplet organelles. Experiments performed using macrophages from TLR-deficient mice have revealed that lipid droplet formation in response to bacteria is dependent on TLR signalling, particularly via TLR2 (Pacheco et al 2002, D'Avila et al 2006, Cao et al 2007, Almeida et al 2009, Mattos et al 2010, 2011b. Moreover, it has been shown that killed bacteria and purified molecules derived from bacteria are also capable of promoting lipid accumulation in treated macrophages (Pacheco et al 2002, Kazemi et al 2005, D'Avila et al In leprosy, the mechanisms of LD formation by ML in Schwann cells share similarities, but also exhibit some differences compared with those observed in macrophages.…”
Section: The Role Of Innate Immune Receptors In Lipid Dropletmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently described the mechanism by which M. leprae induces lipid droplet formation in macrophages and Schwann cells (5,7,28), showing that host-derived cholesterol represents the major lipid component inside these organelles. The importance of lipids in M. leprae energetic metabolism is further supported by the high prevalence of genes involved in lipid anabolism and catabolism, despite the huge reductive evolution that occurred in its genome, producing essentially a minimal gene set for survival (14).…”
Section: Discussionmentioning
confidence: 99%